Synthesis and Properties of Polysilsesquioxanes Having Ethoxysulfonyl Group as a Side Chain - Takahiro Gunji; Kazuki Yamamoto; Akira Tomobe; Noritaka Abe; Yoshimoto Abe (International Journal of Polymer Science)
Polysilsesquioxane having an ethoxysulfonyl group as a side chain was synthesized to prepare a proton-conductive film composed of a main chain of siloxane. At first, sodium 4-(2-methylallyloxy)benzenesulfonate was chlorinated with thionyl chloride. Next, hydrosilylation with trichlorosilane was carried out in the presence of platinum catalyst followed by treatment with ethanol. Finally, the hydrolytic polycondensation was carried out to provide poly(3-(4-ethoxysulfonylphenoxy)-2-methylpropyl)silsesquioxane. This polysilsesquioxane was heated to form a free-standing film that was brittle and brown in color.